Implementation of the Smart Indonesia Programme Policy at Cakrataruna State Elementary School, Cigalontang District, Tasikmalaya Regency, West Java During the Covid-19 Pandemic - Anida Sri Rahayu Mastur (Kybernan: Jurnal Studi Kepemerintahan, 2021)
Covid-19 has caused various kinds of problems not only in Indonesia but also in the world. A lot of assistance has been given to reduce the economic impact of the Covid-19 pandemic. One of them is the Smart Indonesia Programme. However, in practice, at SDN Cakrataruna, Cigalontang District, Tasikmalaya Regency, West Java, there are still some targets that have not been achieved related to this programme. This study uses descriptif qualitatif data analysis techniques and data collection obtained through observation and interviews with purposive sampling technique. The results of the study show that from the variable size/standard policy, it has not been fully achieved, but in terms of policy objectifs, it has been achieved in accordance with the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 10 of 2020 concerning the Smart Indonesia Programme. Human resources are in accordance with the required criteria as well as facilities and infrastructure resources that are still suitable for use. However, the funding resources are still not maximized. The characteristics of implementing agents are in accordance with the main tasks and functions but have not worked optimally because policy implementers have difficulty controlling the use of PIP funds by parents during the Covid-19 pandemic. The attitude or tendency of the implementers to respond positifly to the PIP programme. Communication between agencies in the organization has been organized and running well, as well as communication between organizations, but communication between the organization and the community, especially with parents of students, has not run optimally. Lastly, the economic and social environment of the students and their parents who receive PIP strongly supports the successful implementation of the PIP, as well as the village political elites who strongly support the existence of this programme.